Digital Capabilities and IT Governance as Drivers of Firm Performance: A Multilevel Study in Emerging Markets - Hamidan, Rusdi; Sitorus, Anwar T; Sucipto, Purwo Agus (Data : Journal of Information Systems and Management, 2025)
This study explores the role of Strategic IT Planning (SITP) in fostering Sustainable Competitive Advantage (SCA) among firms operating in emerging economies. With the rapid pace of digital transformation reshaping global competition, aligning IT strategy with business goals has become critical. Drawing on a combination of primary and secondary datasets, the research examines the impact of SITP maturity on firm performance, the mediating influence of digital capabilities, and the moderating role of national digital readiness. The methodology includes firm level survey data integrated with national indicators across multiple emerging markets. Hierarchical Linear Modeling (HLM) is employed to analyze multi level panel data, capturing the nested relationships between organizational practices and country level digital infrastructure. The study applies Structural Equation Modeling (SEM) to validate the effects of SITP on SCA through digital capabilities. Results indicate that higher levels of SITP maturity significantly correlate with improved firm performance and long term competitive positioning. Digital capabilities such as ERP, CRM, and analytics mediate this relationship by enhancing business alignment and operational coherence. Furthermore, the National Readiness Index (NRI) and digital infrastructure metrics moderate the effectiveness of SITP, with distinct cutoff points observed across countries. The findings underscore the importance of aligning internal IT governance structures with external digital environments. Policymakers are encouraged to support firms through investments in infrastructure, cybersecurity, and workforce development. Meanwhile, firms are advised to adopt flexible, data driven strategic planning practices.